2023
DOI: 10.3389/fnagi.2023.1277731
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome-wide association study of quantitative biomarkers from the Alzheimer’s Disease Neuroimaging Initiative study

Kai-Wen Wang,
Yu-Xin Yuan,
Bin Zhu
et al.

Abstract: IntroductionAlzheimer’s disease (AD) is a complex neurodegenerative disease with high heritability. Compared to autosomes, a higher proportion of disorder-associated genes on X chromosome are expressed in the brain. However, only a few studies focused on the identification of the susceptibility loci for AD on X chromosome.MethodsUsing the data from the Alzheimer’s Disease Neuroimaging Initiative Study, we conducted an X chromosome-wide association study between 16 AD quantitative biomarkers and 19,692 single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 130 publications
0
1
1
Order By: Relevance
“…Some patients suffering from this disease can exhibit cognitive impairment, and a shift towards amyloidogenesis in memory-specific brain regions was found in mice mutated in the DMD gene (mdx mouse) compared to wild-type mice 34 . Additionally, the DMD rs5927116 variant was reportedly associated with the volume of entorhinal cortex in a small sample (N = 792); however, this signal is 1.4 Mb away from our AD signal and the variants are independent (LD measured by r 2 < 0.2) 35 .…”
Section: Discussioncontrasting
confidence: 67%
“…Some patients suffering from this disease can exhibit cognitive impairment, and a shift towards amyloidogenesis in memory-specific brain regions was found in mice mutated in the DMD gene (mdx mouse) compared to wild-type mice 34 . Additionally, the DMD rs5927116 variant was reportedly associated with the volume of entorhinal cortex in a small sample (N = 792); however, this signal is 1.4 Mb away from our AD signal and the variants are independent (LD measured by r 2 < 0.2) 35 .…”
Section: Discussioncontrasting
confidence: 67%
“…Historically understudied, sex chromosomes are becoming a new focus for the investigation of sex-specific differences in AD. X chromosome instability has been associated with AD, and X chromosome-related studies have identified loci that are associated with AD risk . X-linked risk could be associated with epigenetic changes (ie, genomic imprinting) such that parent-specific epigenetic modifications are passed to offspring .…”
Section: Discussionmentioning
confidence: 99%